Natural Mineral Water–Plant Extract Combinations as Potential Anti-Aging Ingredients: An In Vitro Evaluation - Carolina P. Gomes; Ana S. Oliveira; Joana Rolo; Tayse F. F. da Silveira; Rita Palmeira de Oliveira; Maria José Alves; Paula Plasencia; Ana Palmeira de Oliveira (Cosmetics, 2025)
Natural mineral waters (NMWs) and plant extracts have long been valued for their therapeutic properties and skin benefits. This study investigated, in vitro, the role of five Portuguese NMWs (A-E), combined with plant extracts from five species (Ficus carica L., Rubus idaeus L., Vaccinium myrtillus, Cistus ladanifer and Thymus x citriodorus) as bioactive ingredients. Antioxidant capacity was assessed using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method. Cellular biocompatibility was evaluated in fibroblasts (L929) and macrophages (RAW 264.7). Skin-repairing and anti-senescence properties were evaluated in L929 cells through the scratch-wound method and β-galactosidase assay. Superoxide dismutase (SOD) was quantified using a commercial kit, and lipopolysaccharide-induced reactive oxygen species (ROS) were quantified using a fluorescent probe (H2DCFDA) in RAW 264.7. The results highlighted the beneficial impact of extracts combined with NMWs. An increase in antioxidant capacity of up to 90% was observed in mixtures comprising Ficus carica L., compared with NMWs alone. In contrast, mixtures with Cistus ladanifer showed promising anti-aging potential, with a 40% decrease in senescent cells and a 33% ROS reduction. Rubus idaeus L. extract produced an increase in cell migration capacity (up to 50%), depending on the NMW. This study highlights the potential synergism of natural ingredients with plant extracts for anti-aging.